Kepemimpinan Pendidikan - Fatonah, Isti (Tarbawiyah Jurnal Ilmiah Pendidikan, 2013)
Leadership or activities lead an effort by someone with all the ability they have to influence, encourage, direct and mobilize the people who led them to set to work with enthusiasm and confidence in achieving its goals. Educational leadership is a readiness, the ability of a person in the process of influencing, encouraging, guiding, directing and mobilizing others to do with the implementation and development of education and teaching so that all activities can be run effectively and efficiently in achieving educational goals.